Left Paraduodenal Hernia Presenting with Atypical Symptoms - Yun, Min Young; Choi, Yun Mi; Choi, Sun Keun; Kim, Sei Joong; Ahn, Seung Ick; Kim, Kyung Rae (Yonsei medical journal, 2010)
Paraduodenal hernias are a rare congenital malformation, but they are the most common internal hernias. They develop secondary to a failure in midgut rotation, which may lead to small bowel obstruction or other clinical manifestations. The authors recently experienced a case of a left paraduodenal hernia presenting with unusual symptoms of left flank pain and vomiting.